2001
DOI: 10.1080/00365540110076688
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Antibacterial Susceptibility, Risk Factors and Outcome of 157 Episodes of Acinetobacter baumannii Bacteremia in 1999 in Slovakia

Abstract: This study prospectively investigated all 157 cases of Acinetobacter baumannii bacteremia occurring in major university hospitals or tertiary care institutions in Slovakia during 1999 in order to determine the antimicrobial susceptibility, risk factors and outcome. Resistance to meropenem was 7.4, gentamicin 35.6, amikacin 26.5, cefepime 20.4 and ciprofloxacin 32.7%, but was only 17.3% to cefoperazone/sulbactam or ampicillin/sulbactam. Antimicrobial susceptibility of A. baumanii was lowest among isolates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Diabetes and prior surgery, which were not significantly associated with overall resistance, were major risk factors in developing resistance in a second (or repeat) isolate. In our studies, many elderly patients who were hospitalized had a sacral decubitus ulcer, and were subsequently found to be infected [32]. These patients had come for a debridement procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and prior surgery, which were not significantly associated with overall resistance, were major risk factors in developing resistance in a second (or repeat) isolate. In our studies, many elderly patients who were hospitalized had a sacral decubitus ulcer, and were subsequently found to be infected [32]. These patients had come for a debridement procedure.…”
Section: Discussionmentioning
confidence: 99%
“…People with diabetes are three times more likely to develop bacterial sepsis and suffer far worse outcomes ( 2 5 ). In particular, diabetes is a risk factor for significantly increased mortality from infections caused by Gram-negative bacteria, especially Acinetobacter baumannii ( 6 9 ). Over a century of literature has indicated that defective phagocytes in diabetic hosts are responsible for worse outcomes from bacterial infections, leading to the characterization of diabetes as an immunosuppressive state.…”
Section: Introductionmentioning
confidence: 99%
“…Eşlik eden hastalıklar Acinetobacter infeksiyonları için risk oluşturabilir ve bazı çalışmalarda kanser kemoterapisi almak Acinetobacter bakteriyemisi için risk faktörü olarak bulunmuştur (10,20). Bu çalışmada da kanser kemoterapisi almış olmak, olgu grubunda kontrol gruplarına göre daha yüksek oranda bulunmuştur.…”
Section: İrdelemeunclassified
“…Acinetobacter bakteriyemisi ve diğer etkenlerle gelişen bakteriyemilerin karşılaştırıldığı bir çalışmada ise kanser kemoterapisi değil ama immüno-süpresyon varlığı bir risk faktörü olarak bulunmuştur (13). Diyabetik hastalarda Acinetobacter infeksiyonlarında mortalitenin daha yüksek olduğu gösterilmiştir (20,21). Diyabet ve infeksiyonun edinilmesi arasındaki ilişki değerlendirildiğinde veriler çelişkili olup, bir çalışmada diyabetin diğer etkenlerin neden olduğu bakteriyemiler için risk oluşturduğu, Acinetobacter bakteriyemisi olan grupta daha az diyabetik hasta olduğu bildirilmiştir (13).…”
Section: İrdelemeunclassified